Assessing the Competitive Advantage of the Association of Volleyball Professionals (AVP) in Events Marketing - Gearhart, Heather (2017)
The purpose of this research is to assess the competitive advantage of the Association of Volleyball Professionals (AVP) in events marketing. In the North American professional sports industry, there are extremely large entities namely the Big 4 – the National Football League (NFL), the National Basketball Association (NBA), Major League Baseball (MLB), and the National Hockey Association (NHL) – who enjoy lucrative recurring revenue streams. It could be said that other professional sports entities in North America remain understudied and left with relatively little resources compared to the Big 4. The research specifically looks at the AVP to answer questions regarding the marketing strategies employed by the league, and another league of similar structure in order to effectively utilise limited resources for strategic positioning within the sport and lifestyle industry. The AVP has been heavily reliant on sponsorship from other firms to survive in the past, and as a league, it is important to understand how to exploit internal resources. Where sponsorship is an external source of competitive advantage, this research assesses the potential points of competitive advantage for the AVP that lie within the firm. A qualitative content analysis was conducted on 14 interviews with the AVP CEO Donald Sun, academic articles concerning competitive advantage, an interview with the National Women’s Soccer League’s (NWSL) director of operations, and goals of the Fédération Internationale de Volleyball (FIVB). An asynchronous online interview was also conducted with an AVP employee and was part of the content analysis. A quantitative survey was subsequently conducted with 162 members of the volleyball community to gather insights on various aspects of the AVP and information on sports consumption. The AVP was found to have an access-based competitive advantage through the development of a pipeline to serve athletes of all ages. The pipeline functions as a revenue stream to help the AVP become more financially stable along with growing the AVP brand and interest in the game of beach volleyball. Sun’s managerial ability led to the creation of the unique and inimitable systematic pipeline which capitalises on the strengths of the firm to serve a larger benevolent purpose. Current marketing strategies of the AVP prove to be in the right channels but can be improved with delivery and providing more access to increase viewership of events. It is hoped that this research will improve the AVP’s ability to function with their resource pool to leverage their brand more effectively and increase the visibility of events, which can potentially be transferred to similar sports organisations.